Integrasi Nilai Budaya dalam Ragam Hias Bali & Yogyakarta untuk Penguatan Karakter Siswa melalui Pembelajaran Seni Rupa - Ganika, Made Aditya Abhi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to examine the integration of cultural values embedded in traditional decorative patterns (ragam hias) from Bali and Yogyakarta as a medium for art education to strengthen students' character. Decorative patterns are not only visual elements in art but also contain philosophical meanings and noble values such as cooperation, perseverance, spirituality, and love for culture.Using a qualitative approach, data were collected through observation, interviews with art teachers, and documentation of classroom learning processes. The data were analyzed using descriptive-interpretative methods to explore how decorative patterns are utilized in art education and how students respond both cognitively and affectively.The results show that integrating Balinese and Yogyakartan decorative patterns into art learning enhances students’ aesthetic understanding and fosters character development such as discipline, responsibility, tolerance, and cultural pride. Culture-based learning is proven to be effective in shaping students' holistic personality.